2000
DOI: 10.1034/j.1399-5448.2000.010204.x
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetic children have abnormal lipid profiles during pubertal years 1

Abstract: Plasma CT levels of type I diabetic children are increased in comparison to non-diabetic children and do not follow the usual decreasing pattern during puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
27
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 14 publications
(16 reference statements)
4
27
1
Order By: Relevance
“…The increased prevalence of DLP has previously been reported, even among young patients (1-3,14). However, the prevalence in the present study was much higher than that found by Polak and cols., who reported that 16% of puberal patients with T1D had elevated TC, while 5% had hypertriglyceridemia (15). Regarding the atherogenic profile, the most commonly reported forms of DLP in patients with T1D include elevated TC, LDL, and TG values (4,6,9) which are similar to the findings observed in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…The increased prevalence of DLP has previously been reported, even among young patients (1-3,14). However, the prevalence in the present study was much higher than that found by Polak and cols., who reported that 16% of puberal patients with T1D had elevated TC, while 5% had hypertriglyceridemia (15). Regarding the atherogenic profile, the most commonly reported forms of DLP in patients with T1D include elevated TC, LDL, and TG values (4,6,9) which are similar to the findings observed in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…also found that dyslipidemia was more common in adolescents than younger children (15), what would be expected based on previous studies (17,18). Females were particularly affected.…”
supporting
confidence: 77%
“…Overweight and obesity were associated with dyslipidemia and total hypercholesterolemia was the most common abnormality. This proportion was higher than that found in other studies (16)(17)(18), even in our population (16). It is probable that the higher rates of dyslipidemia in this study are explained by the higher HbA1c levels presented by this sample, although information about TSH levels and proportion of statin users are lacking in the paper and would be important to interpret these data.…”
contrasting
confidence: 75%
“…Dyslipidemia frequency in diabetic children varies between 3.8% and 72.5% in different studies [14][15][16][17][18][19], and hypercholesterolemia was reported as the most frequent finding [16,[19][20][21]. Redondo et al found a dyslipidemia prevalence of 3.8% in the US with 11,348 T1D patients aged 2-18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Another study determined that girls had higher lipid levels, among which hypercholesterolemia was the most common, and that age, diabetes duration, increased BMI and A 1C levels were associated with lipid anomalies [24,35]. Polak et al investigated abnormal lipid profiles in children with T1D during puberty and described that cholesterol levels were not associated with metabolic control, while triglyceride levels could have a weak correlation with metabolic control [19]. Heyman et al studied the relationship among diet, physical activity and metabolic control in adolescent girls late in puberty and reported that unhealthy diets and low physical activity lead to impaired metabolic control and increased lipid levels [27].…”
Section: Discussionmentioning
confidence: 99%